Formation of communicative skills of adolescents in the process of practicing theatrical improvisation - Elena P. Shan'gina (Управление культурой)
The purpose of the study is to consider the role of stage improvisation as a tool for the formation of adolescents' communication skills. An analysis of the theoretical literature on the psychology of adolescence, social psychology, and studies of the communicative qualities of adolescents showed the significant role of the communication process at this age stage. The effectiveness of interpersonal interaction among adolescents is associated with the formation of I - the concept of personality, adequate positive self-esteem; the possibility of satisfying emotional needs and the need for belonging to a group, building relationships of friendship and love. Formed communication skills and abilities have a positive effect on the psychological health of a teenager and the harmony of his personal development. To describe the development of communication skills in the classroom for stage improvisation, the role and functions of the communication process in adolescence, the relationship between the concepts of communication and communication, the stages of the skill formation process, the potential of cultural and creative activities and leisure communication for the development of the components of the communication process are considered, the formed communication skills and basic requirements for conducting classes. This paper proves that the formation of communication skills that contribute to meeting the actual needs of adolescents, taking into account their psychological and age characteristics, is possible within the framework of stage improvisation classes. The results of the study can be used in the work of teachers of institutions of additional art education.